The role of fibroblast growth factor 23 and Klotho in uremic cardiomyopathy. Issue 4 (July 2016) - Grabner, Alexander; Faul, Christian
Abstract : Purpose of review: In chronic kidney disease (CKD), multiple factors contribute to the development of cardiac hypertrophy by directly targeting the heart or indirectly by inducing systemic changes such as hypertension, anemia, and inflammation. Furthermore, disturbances in phosphate metabolism have been identified as nonclassical risk factors for cardiovascular mortality in these patients. With declining kidney function, the physiologic regulators of phosphate homeostasis undergo changes in their activity as well as their circulating levels, thus potentially contributing to cardiac hypertrophy once they are out of balance. Recently, two of these phosphate regulators, fibroblast growth factor 23 (FGF23) and Klotho, have been shown to affect cardiac remodeling, thereby unveiling a novel pathomechanism of cardiac hypertrophy in CKD. Here we discuss the potential direct versus indirect effects of FGF23 and the soluble form of Klotho on the heart, and their crosstalk in the regulation of cardiac hypertrophy. Recent findings: In models of CKD, FGF23 can directly target cardiac myocytes via FGF receptor 4 and induce cardiac hypertrophy in a blood pressure-independent manner. Soluble Klotho may directly target the heart via an unknown receptor thereby protecting the myocardium from pathologic stress stimuli that are associated with CKD, such as uremic toxins or FGF23. Summary: Elevated serum levels of FGF23 and reduced serum levels of soluble Klotho contribute to uremic cardiomyopathy in a synergistic manner.